Answer: p = 5, p = 1
Step-by-step explanation
Given
![x^2−3x+1=p\left(x−3\right)](https://img.qammunity.org/2023/formulas/mathematics/college/7ejxv0da5ycpzflf034chsep2tj1rs1wk7.png)
Since the roots are equal, then the discriminant must be 0:
![b^2-4ac=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/olq7wwt42xmcwpf6bsxtg4i3fenox9psvr.png)
where a, b and c are the coefficients of the quadratic expression in the form ax² + bx + c = 0. Then, we must rearrange our equation in the previous form.
0. Multiplying ,p, times the expression inside the parenthesis:
![x^2−3x+1=p\cdot x−3p](https://img.qammunity.org/2023/formulas/mathematics/college/rnnbokvqsscf06gh3kpdart9t9h3i2978j.png)
2. Setting the expression to 0:
![x^2−3x-px+1+3p=0](https://img.qammunity.org/2023/formulas/mathematics/college/ol4wy0bnz8nybrto3tpipqmjl6c48t7n4c.png)
2. Simplifying the expression by grouping similar terms:
![x^2-(3+p)x+(1+3p)=0](https://img.qammunity.org/2023/formulas/mathematics/college/8k8po4q92tn216tzz1b8mqymtar637ft68.png)
Then, in our case: a = 1, b = –(3 + p), and c = (1 + 3p).
Now, we can replace the value in the discriminant and solve for p:
![(-(3+p))^2-4(1)(1+3p)=0](https://img.qammunity.org/2023/formulas/mathematics/college/zcjjwfyo0txocchda54njfktnkkuh01zpc.png)
![(-3-p)^2-4(1+3p)=0](https://img.qammunity.org/2023/formulas/mathematics/college/boh8ggft6mbgn78p78yzos7oo58xzbllb9.png)
![(-3-p)^2-4+12p=0](https://img.qammunity.org/2023/formulas/mathematics/college/6k0vv2m1isyck1rihbw52ep2t5f6yom5gz.png)
![p^2-6p+5=0](https://img.qammunity.org/2023/formulas/mathematics/college/mmtske1x27vsns7ujpcudao6ppz36eegd0.png)
Finally, we can use the General Quadratic Expression to solve for p:
![p_(1,2)=(-(-6)\pm√((-6)^2-4(1)(5)))/(2(1))](https://img.qammunity.org/2023/formulas/mathematics/college/tlk62fiekmgfqmf0qhm9da0ntwqaugx820.png)
![p_(1,2)=(6\pm√(36-20))/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/k42v751rlwm62gaysvpxm2m6w3c1asyuru.png)
![p_(1,2)=(6\pm√(16))/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/msttkbbvxfesiaksocfbej394pzampqjov.png)
![p_(1,2)=(6\pm4)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/cdi5o6j25qcmvahzc08hjd3j7qfgc39or4.png)
Now, calculating both results:
![p_1=(6+4)/(2)=(10)/(2)=5](https://img.qammunity.org/2023/formulas/mathematics/college/3tnox2ei0i29i67710cav5n8axvvju4liq.png)
![p_1=(6-4)/(2)=(2)/(2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/whe11e4no9daqlrveuvjmkkat433izx14t.png)